Logistics capabilities and customer satisfaction nexus: Examining the dual mediating effects of logistics service quality and assurance quality in modern supply chain management - Afiifah Khoiriyyah; Ika Nurul Qamari; Wan Hasmat Wan Hasan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of logistics capability on customer satisfaction with logistics service quality and assurance quality as mediating variables in the context of logistics in Indonesia, which is currently experiencing a decline in ranking in the Logistics Performance Index. Using a quantitative approach, the study was conducted through a survey method with 200 online shop respondents on the Shopee platform and analyzed using the Structural Equation Model. The study's results indicate that logistics capability does not directly affect customer satisfaction but positively affects logistics service quality and assurance quality. Logistics service quality and assurance quality positively impact customer satisfaction and can mediate the effect of logistics capability on customer satisfaction. These findings imply that logistics service companies need to improve their logistics capabilities while ensuring good service quality and assurance to achieve optimal levels of customer satisfaction. The study provides theoretical and practical contributions to developing strategies to improve customer satisfaction in the logistics industry, increase global competitiveness, and foster sustainable customer relationships in a dynamic digital era.